CITY PARK DESIGN CRITERIA TO CREATE RESILIENT CITY PARKS Case Study: City Park in Surabaya - Ekky Nada Wijaya; RA Retno Hastijanti; Darmansjah Tjahja Prakasa (International Conference of Innovation and Community Engagement, 2024)
The increase in population growth in an area encourages diversity in aspects of land use. The lack of presence in the Green Open Space (RTH) area affects the quality of life of the community in an area. In the Regulation of the Minister of Public Works in 2008, it is stated that one form of utilization of Green Open Space (RTH) for the city/urban area scale is the RTH of the City Park. Urban parks in their provision and management are public Resilient public spaces are open areas that help cities become more resilient overall as urban ecosystems in a number of ways, including lessening the effects of climate change, lowering the hazards and vulnerabilities of the urban environment, and fostering social cohesion. (Kotzamani, E.-E., & Alexandri, E. 2019) This research aims to identify how the design criteria of a city park are, in terms of realizing a resilient city park. Through a qualitative approach, the first analysis is to review the theories related to the conception of resilient urban park design. Second, analyze the aspects of the conception of resilient city park design in the sampling of city park areas in Surabaya. Third, to prepare urban park design criteria that can realize and maintain sustainability while improving the quality of life of the community. The results of the study show that, first, it finds indicators of the resilience of a city park. Second, the findings of indicator identification based on the conditions and characteristics of city park sampling in Surabaya. Third, finding design criteria such as the minimum area that must be planted or covered by vegetation, vegetation density, the proportion of the park area greater than the pavement, the availability and quality of infrastructure, cleanliness and maintenance maintained, waste processing, a wider target of users, the availability of facilities for various visitor activities, ease of access, the provision of inclusive social spaces, sufficient lighting and community participation in planning and Park management can increase a sense of ownership and sustainability. These criteria can help in creating resilient city parks to improve the quality of life of urban people.